Dexamethasone-Induced Insulin Resistance Impaired Artemin Levels in the Hippocampus and Altered Behavioural Patterns - Çalışkan, Hasan (Scripta Medica, 2025)
Background/Aim: Insulin resistance (IR), a hallmark of metabolic syndrome, contributes to glucose dysregulation, obesity, dyslipidaemia and hypertension. While the systemic effects of IR are well-documented, its impact on neurotrophic factors such as artemin (ARTN) remains unclear. This study investigates the relationship between IR-induced metabolic dysfunction, ARTN expression in specific brain regions and associated behavioural alterations.Methods: Sixteen male Wistar rats were used (control and an insulin resistance (IR) group, each group n = 8). The IR group received intraperitoneal dexamethasone (1 mg/kg/day) for five days to induce IR. Behaviours were evaluated using the open-field test. Metabolic profiling included blood glucose, serum insulin and HOMA-IR calculations. ARTN levels were analysed in the prefrontal cortex (PFC), striatum, hippocampus and serum.Results: Dexamethasone-treated animals displayed pronounced anxiety-like behaviours and metabolic deterioration (elevated glucose, insulin resistance). While ARTN levels in the PFC, striatum and serum remained unchanged between groups, hippocampal ARTN was remarkably lower in the IR group compared to controls.Conclusion: Early-stage IR selectively reduces hippocampal ARTN levels, accompanied by increased anxiety and decreased locomotor activity. These findings suggest a region-specific vulnerability of ARTN to metabolic dysfunction, warranting further investigation into its neuroprotective role in the progression of IR.